N11 Patients' challenges of living with, and managing inflammatory bowel disease: a meta-synthesis. (25th January 2019) - Byron, C; Cornally, N; Burton, A; Savage, E
Abstract: Background: IBD can impact negatively on patients' lives, creating challenges for those affected. From previous research, these challenges tend to increase with disease activity (Jelsness-Jorgensen et al. 2011). Common challenges identified by patients affected by IBD include disease-related symptoms such as loose bowel motions, fatigue (Loven Wickman et al. 2016) and a lack of knowledge regarding their disease (Lesnovska et al. 2013). The psychological well-being of those with IBD may also be adversely affected, causing challenges for patients (Devlen et al. 2014; Argyriou et al. 2017; Sun Kim et al. 2017). It is postulated that an enhanced comprehension of patients' challenges may lead to the development of mechanisms to enhance patient-related outcomes (Pittet et al. 2016), the development of self-management interventions (Irvine 2004) and improvements in patients' quality of life (Casati et al. 2000). A meta-synthesis of all available published qualitative literature on the challenges of patients living with IBD and there management of these is warranted in order to establish a comprehensive account of the body of evidence published to date. The aim of this meta-synthesis was to examine qualitative studies and data which reported on patients' challenges of living with and managing IBD focussing on the following research questions: What are the main challenges experienced by patients with IBD in their everyday lives? What impact do these challenges have on patients' lives? What strategies do patients use to manage the main challenges experienced? Methods: Searches were conducted in five databases to locate articles deemed eligible for inclusion. The search resulted in the screening of 1, 413 studies, of which, 13 studies were deemed eligible for inclusion. Results: Four themes were identified from the literature extracted through thematic analysis; the unpredictability of living with IBD, the emotional turmoil of living with IBD, the social side of living with IBD and striving to maintain a normal life in managing IBD. Conclusions: Patients with IBD experience many challenges including physical symptoms, long-term effects of IBD, lack of support, change of role within their domestic and social environments including school and work settings. The collective impact of these challenges were identified are social exclusion and poor psychological well-being. Data regarding the management of the challenges experienced was notably lacking although some evidence of 'striving towards normality' was apparent. This meta-synthesis has highlighted the compelling need to review and modify individual care plans to enhance the patients' lived experiences of IBD and develop interventions to assist patients with self-management.